Pengaruh Personal Growth Initiative Terhadap Psychological Distress Pada Mahasiswa Tahun Pertama di Universitas Negeri Makassar - Safitri, Desi Ayu; Ridfah, Ahmad; Cahyaningrum, Kartika (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the effect of personal growth initiative on psychological distress in first year students at Makassar State University. The respondents in this research were 418 first year students, Class of 2023, representing all faculties at Makassar State University. The results of data analysis using exponential regression analysis showed a significance value of 0.631, meaning that there was no influence of personal growth initiative on psychological distress in first year students at Makassar State University. The implication of this research is that it can contribute to the development of knowledge related to personal growth initiative and psychological distress.